Влияние давления в плазмохимическом реакторе на процесс плазменной обработки растворов хлорида натрия - Захаров, Р. И.; Калашникова, А. Н.; Пивоваров, А. А.; Николенко, Н. В. (НТУ "ХПИ", 2014)
Методом математического моделирования и экспериментально изучено влияние давления в плазмохимическом реакторе на процесс синтеза смесей Н2О2 и ClO2. В качестве параметров оптимизации рассматривали селективность процесса, его скорость и энергозатраты. Определено оптимальное давление и оптимальная продолжительность процесса плазменной обработки растворов NaCl. Для диапазона давлений от 0,1 до 1 атм экспериментально подтверждены рассчитанные величины оптимального времени, при которых достигается максимальная селективность процесса по хлорит-ионам.

The method of mathematical modeling and experimentally was studied the effect of pressure in the plasma-chemical reactor for the synthesis of mixtures of H2O2 and ClO2. The parameters optimization process was considered the selectivity, speed and power consumption. The optimal pressure and the optimal duration the process of plasma treatment of NaCl solution were determined. For the pressure range from 0.1 to 1 atm experimentally was confirmed the calculated values of the optimal time at which is achieved the maximum selectivity by the process of chlorite ions. It has been shown that the synthesis method of oxidizing plasma treatment solutions of sodium chloride are optimally carried out at atmospheric pressure, this ensures a sufficiently high yield of the total oxidant concentration at the greatest amount of sodium chlorite as the most valuable product of the synthesis. While is maintaining a relatively high rate of the process at the lowest cost of electricity.
The effect of pressure in the plasma-chemical reactor for process of plasma treatment solutions of sodium chloride
Keywords: плазма; контактная неравновесная плазма; давление; хлорит; реактор; plasma; chlorite; reactor; sodium chloride